ORGANIZATIONAL COMMITMENT AND WORK DISCIPLINE - Mukmin Pohan (CERED Indonesia Institute, 2021)
This study aims to determine the effect of organizational commitment and work discipline on the performance of employees of PT. PLN (Persero) Main Unit for North Sumatra Region. This research approach uses an associative and quantitative approach. The sampling technique used a sampling technique using the slovin formula totaling 65 people. The data collection technique used in this study used a questionnaire/questionnaire and interview techniques. The data analysis technique in this study uses Multiple Linear Regression, Classical Assumption Test, Hypothesis Testing (t-test and f-test) and Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package For the Social Sciences) software version 16.0. The results showed that simultaneously organizational commitment and work discipline had a positive and significant effect on the performance of PT. PLN (Persero) Main Unit for North Sumatra Region. Based on the partial test, it shows that the organizational commitment variable has a positive and significant effect on employee performance, and the work discipline variable has a positive and significant effect on the performance of PT. PLN (Persero) Main Unit for North Sumatra Region.